Da cerâmica ao corpo, do corpo ao gênero: sepultamentos com vasilhames do sítio Justino - Oliveira, Lucas Santos (2022)
Since the identification and excavation of the Justino site in the early 1990s, the group of burials has been the subject of numerous researches that have advanced pertinently in the understanding of the funerary practices that took place there over thousands of years (between 9.000 years BP to the 17th century). Among the different ways of burying the dead, the deposition of ceramic vessels on specific parts of the body, which served as a funerary wrapping or which were simply placed next to the deceased, intrigued researchers in previous assessments, however, such researches did not delve into the socio-symbolic aspects that such associations could have towards the dead, presenting only the techno-typological descriptions of these artifacts and, in a few cases, demonstrating that the individuals who received vessels would present themselves in life with some kind of high status. Ahead the possibilities, we seek to extrapolate such inferences through the approaches of Gender and Indigenous History to understand whether such accompaniments could demarcate possible gender performativities. With the collection of data about the bodies of the deceased (sex, age, pathologies), the ways of burying the dead (position of the body, limbs, skull and face, types of inhumation and graves) and, finally, the good graves, all of these aspects subsidized according to ethno-historical and ethnographic information, we were able to understand that some specific parts of the dead body would be symbolically more relevant and that, in front of the number of individuals who received these mortuary vases, which permeated only 16% of Justino's burials, we identified that these people would have prominent social roles, such as shamans, musicians and/or instrumentalists, warriors, leaders, among others. These results demonstrate that it is not appropriate to think that this social relevance was attributed solely to a single sexual category and that other forms of identities were linked to gender performativities in the past of the lower São Francisco.